# Match the post#

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0!+1-2+3+4^5+6*7 + 8*9 = 1141$$

$$\displaystyle 9*87 +6*54+32+1+0!=1141$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0+1*2+345+6+789 = 1142$$

$$\displaystyle 9*8+7*6+5-4+3+2^{10}=1142$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0!+1*2+345+6+789 = 1143$$

$$\displaystyle 9*8+7*6-5+4+3!+2^{10}=1143$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0!+1+2+345+6+789 = 1144$$

$$\displaystyle 9*8+7*6+5-\sqrt{4}+3+2^{10}=1144$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0-1+234*5-(6+7+8)-\sqrt{9} = 1145$$

$$\displaystyle 9*8+7*6-5+4*3+2^{10}=1145$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0!-1+234*5-(6+7+8)-\sqrt{9} = 1146$$

$$\displaystyle 9+8*7-6+543*2+1+0=1146$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0 +1+234*5-(6+7+8)-\sqrt{9} = 1147$$

$$\displaystyle 9+8*7-6+543*2+1+0!=1147$$

(I'm off now to get a life!!)

Last edited:

#### Denis

##### Senior Member
01234 - 5 + 6 - 78 - 9 = 1148

987 - 6 + 54*3 + (2 + 1)! - 0! = 1148

See you in Murgatroyd Harriet!

#### ksdhart2

##### Senior Member
$$\displaystyle 0! + 1234 - 5 + 6 - 78 - 9 = 1149$$

$$\displaystyle 9 \cdot 8 \cdot 7 + 6 + 5 \cdot 4 \cdot 32 \cdot 1 - 0! = 1149$$

#### Denis

##### Senior Member
012 + 34 - 5! + 6! + 7*8*9 = 1150

9*8*7 + 654 - 3^2 + 1 + 0 = 1150

#### ksdhart2

##### Senior Member
$$\displaystyle -0! + 12 + 345 + 6 + 789 = 1151$$

$$\displaystyle 9 \cdot 8 \cdot 7 + 6 + 5 \cdot 4 \cdot 32 \cdot 1 + 0! = 1151$$

#### lookagain

##### Senior Member
0 + 12 + 345 + 6 + 789 = 1152

9*8*7 + 6 + 5*4*32 + 1 + 0! = 1152

#### ksdhart2

##### Senior Member
$$\displaystyle 0! + 12 + 345 + 6 + 789 = 1153$$

$$\displaystyle 9 + 8 + 7 \cdot 6 \cdot (5 + 4) \cdot 3 + 2 \cdot 1 + 0 = 1153$$

#### mmm4444bot

##### Super Moderator
Staff member
0 + 1234 - 5 * (6 - 7 + 8 + 9) = 1154

9 + 8 + 7 * 6 * (5 + 4) * 3 + 2 * 1 + 0! = 1154

$$\;$$

#### ksdhart2

##### Senior Member
$$\displaystyle 0! + 1234 - 5 \cdot (6 - 7 + 8 + 9) = 1155$$

$$\displaystyle 9 + 8 + 7 \cdot 6 \cdot (5 + 4) \cdot 3 + 2 + 1 + 0! = 1155$$

#### Otis

##### Senior Member
(0! + 1)^2 * (3 - 4 + 5 + 6 + 7) * (8 + 9) = 1156

9 + 8 + 7 * 6 * (5 + 4) * 3 + (2 + 1)! - 0! = 1156

$$\;$$

#### ksdhart2

##### Senior Member
$$\displaystyle 0 + 1 \cdot 2 + 345 + 6 \cdot (7 + 8) \cdot 9 = 1157$$

$$\displaystyle 9 + 8 + 7 * 6 * (5 + 4) * 3 + (2 + 1)! - 0 = 1157$$

#### Denis

##### Senior Member
((0 + 1 + 2)!)! + 3! + 456 - 7 - 8 - 9 = 1158

-9 -8 +7*65*(4 - 3) + ((2 + 1 + 0)!)! = 1158

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0+1+234*5-6-7-8+9 =1159$$

$$\displaystyle (9*8+7-6+543*2)*1+0=1159$$

#### Harry_the_cat

##### Senior Member
$$\displaystyle 0!+1+234*5-6-7-8+9 =1160$$

$$\displaystyle (9*8+7-6+543*2)*1+0!=1160$$